Cyber Warfare: A Serious Threat to Global Security - Verma, Pushp Lata (SCHOOL SCIENCE, 2015)
The fast-changing pace of information and communication technology has changed the way how we communicate, collaborate, share information and do business. In this age, wherein online communication has become the norm, Internet users and governments face increased risks of becoming the targets of cyber attacks. The new information technologies have posed threats in the form of transnational terrorism, international organised crime, cybercrime or hostile information operations directed against national or global interests. For the individual, the risks include confidentiality of their personal and private communications and use of their personal information for unlawful activities. At national levels, cyber war has the potential to paralyse crucial government installations and institutions having serious social and financial ramifications